Formalin evokes calcium transients from the endoplasmatic reticulum - Fischer, Michael; Soller, Kailey J.; Sauer, Susanne; Kalucka, Joanna; Veglia, Gianluigi; Reeh, Peter (PLoS ONE, 2015)
The formalin test is the most widely used behavioral screening test for analgesic compounds. The cellular mechanism of action of formaldehyde, inducing a typically biphasic pain-related behavior in rodents is addressed in this study. The chemoreceptor channel TRPA1 was suggested as primary transducer, but the high concentrations used in the formalin test elicit a similar response in TRPA1 wildtype and knockout animals. Here we show that formaldehyde evokes a dose-dependent calcium release from intracellular stores in mouse sensory neurons and primary keratinocytes as well as in non-neuronal cell lines, and independent of TRPA1. The source of calcium is the endoplasmatic reticulum and inhibition of the sarco/endoplasmic reticulum calcium-ATPase has a major contribution. This TRPA1-independent mechanism may underlie formaldehyde-induced pan-neuronal excitation and subsequent inflammation.
EVALuna2:2473